HUBUNGAN ASUPAN MAKANAN, AKTIVITAS FISIK DAN PENGGUNAAN KONTRASEPSI HORMONAL DENGAN KADAR KOLESTEROL DARAH (Studi pada Wanita Keluarga Nelayan Usia 30 – 40 Tahun di Tambak Lorok, Semarang Tahun 2017) - Putri Nurul Agustyanti; Siti Fatimah Pradigdo; Ronny Aruben (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Hypercholesterolaemia is a condition of high cholesterol level in blood. Prevalence of hypercholesterolaemia in Indonesia aged 25-34 is 9,3%, aged 55-64 is 15,5%. In women, prevalence of hypercholesterolaemia is 14,5%. The purpose of this research was to analyze the correlation of food intake (fat, cholesterole, fiber intake), physical activity and use of hormonal contraceptives with blood cholesterol level on women in fisherman’s family aged 30-40 years old in Tambak Lorok. This was an explanatory research with cross sectional study. Sampling technique was using purposive sampling with 40 respondents. Examination of blood cholesterole level was using CHOD_PAP method with semi automatic device. Statistical trial which was used in this research was Rank Spearman Test and Fisher’s Exact Test, p < 0,05. Mean of total fat intake was 93,85% classified as good (80%-100%). Mean of cholesterol intake was 249,65 mg/day classified as recommended (≤ 300 mg/day). Mean of fiber intake was 8,33 gr/day and classified as low (<30 gr/day). Mean of PAL physical activity was 1,61 and classified as light (1,40-1,69). From 40 respondents, 52% were using hormonal contraceptive. The results showed that there were correlation of fat intake, cholesterole intake, physical activity, use of hormonal contraceptive with blood cholesterole level (p <0,05) and there were no correlation of fiber intake with blood cholesterole level (p> 0,05). Recommended community to manage intake of food low fat and low cholesterole diet, increased fiber intake by eating more fruits and vegetables, for adult women could use non hormonal contraceptive to reduce blood cholesterole level.